Variability of lexicographic definitions as a reflection of the dynamic nature of lexical meaning - Tur, Vitali V. (Journal of the Belarusian State University. Philology, 2021)
An approach to the nature of lexical meaning is justified, according to which its structure and boundaries are formed in the process of communication. On this basis, a new look at lexicographical discourse is proposed, the latter being an important source of empirical data on the boundaries and types of variability of lexical meaning in the language. The paper presents the results of a comparative analysis of the dictionary definitions of the names of clothes, weapons and culinary names in English, which was carried out on the material of five dictionaries. The aim of the analysis is to identify types of variability of the component structure and the boundaries of senses described in lexicographic definitions. The features of the five identified types of variability in the semantic descriptions are revealed: the interchangeability of differential features implicating each other; the mismatch of the information saturation of the same semantic regions; the variability of categorical features; the variability of semantic frames; splitting the same semantic regions into different number of senses and sub-senses. It is concluded that it is impossible to represent a meaning in the form of the only true set of features – the structure and boundaries of lexical meaning depend on many variable factors, in particular, on the speaker’s chosen strategy for representing this meaning, the features selected as the core, the principles of delimiting the meaning from other semantically close categories, etc.